Clinical and Analytical Characterization of the DiaSorin and ScheBo Fecal Pancreatic Elastase 1 Assays. Issue 3 (March 2022) - Wyness, Sara P.; Nelson, Heather A.; Jensen, Ryan; Bird, Joseph; Norgyal, Tenzin; Hall, Hailey; Johnson, Lisa M.
Abstract : Objectives: Fecal pancreatic elastase (PE) assays are screening tests for exocrine pancreatic insufficiency (EPI). We analytically evaluated a new PE assay and retrospectively analyzed data from an academic hospital and reference laboratory to understand the clinical utility. Methods: Forty stool samples with different PE concentrations were tested on the ScheBo enzyme-linked immunosorbent assay (ELISA) versus DiaSorin LIAISON immunoassay; a simple-to-use extraction device was assessed. The cross-reactivity of porcine enzymes was investigated in the immunoassay. Charts of 207 patients with PE results less than 250 μg/g at an academic hospital were reviewed, and data were analyzed for 5136 patients with repeat PE results from a reference laboratory. Results: The LIAISON immunoassay gave comparable results to the ScheBo ELISA, with 87.5% agreement of PE results in classifying as sufficient, mild/moderate insufficiency, or severe insufficiency. The extraction device worked well compared with manual weighing, and no cross reactivity with porcine enzymes was observed. In agreement with prior studies, our clinical data suggested that PE assays were most useful in detecting severe EPI. Conclusions: The new DiaSorin LIAISON immunoassay preforms similarly to the well-known ScheBo ELISA. Pancreatic elastase assays can help identify patients with severe EPI but are not as useful in classifying mild/moderate EPI.